The Effect of Differentiated Learning on Improving Student Learning Outcomes - Aguanda; Setiawan, Agus; Anwar, M. Saidun; Wardana , Muhammad Rafli Faishal; Yambasu, Rebecca Alicia (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
This research aims to obtain objective information and examine differences in the abilities of reasoning mathematical students who study with method learning differentiate assistance with RME-based matrix teaching materials from students who use conventional methods. This research uses a quantitative approach with experimental research methods pseudo (quasi-experiment) with type non-equivalent control groups design. The study was carried out in the even semester of the 2022/2023 academic year in the mathematics subject matrix material. The subjects in the research involved students of class XI APHP at SMK Negeri 2 Metro Lampung consisting of class XI APHP 1 as the experimental class and XI APHP 2 as the control class. In the study, the data collected used test beginning (pretest) and the final (posttest) given to the experimental style, and the control class consisted of 4 essay questions. The statistical data obtained were normality, homogeneity, and hypothesis tests, which were processed using the SPSS 16.0 program. Based on the results of the hypothesis test, a significance value (2- 2-tailed) was obtained of 0.000. Therefore, the significance value was <0.05, so it can be concluded that the results of this research show that there is an influence of differentiated learning assisted by RME-based matrix teaching materials on mathematical reasoning abilities. class XI APHP student at SMK Negeri 2 Metro Lampung.